Х^4 - 6х^2 - 27 = 0
Х^2 = а ; а > 0
а^2 - 6а - 27 = 0
D = 36 + 108 = 144 = 12^2
a1 = ( 6 + 12 ) : 2 = 9
a2 = ( 6 - 12 ) : 2 = - 3 ( < 0 )
X^2 = 9
X1 = 3
X2 = - 3
Ответ 3 ; - 3
4) |x|=6,3 : 7; 6) |x|=4.2 : 5;
|x|=0.7; |x|=0.84;
x=0.7 или x= -0.7 x=0.84 или x= -0.84
Ответ: x= -0.7; 0.7 Ответ: x= -0.84; 0.84
5)6*|x|=6.9+2.7; 7) 4*|x|=2.2-0.6;
6*|x|=9.9; 4*|x|=1.6;
|x|=9.9 : 6; |x|=1.6 : 4;
|x|=1.65; |x|=0.4;
x=1.65 или x= -1.65 x=0.4 или x= -0.4
Ответ: х= -1.65; x=1.65; Ответ: x= -0.4; 0.4
Привести к общему знаменателю а потом по действиям
Ответ : 1, 2, 6, 7, 3, 4, 1, 5.